2011
DOI: 10.1002/pssr.201105410
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial CVD growth of sp2‐hybridized boron nitride using aluminum nitride as buffer layer

Abstract: Epitaxial growth of sp2‐hybridized boron nitride (BN) using chemical vapour deposition, with ammonia and triethyl boron as precursors, is enabled on sapphire by introducing an aluminium nitride (AlN) buffer layer. This buffer layer is formed by initial nitridation of the substrate. Epitaxial growth is verified by X‐ray diffraction measurements in Bragg–Brentano configuration, pole figure measurements and transmission electron microscopy. The in‐plane stretching vibration of sp2‐hybridized BN is observed at 136… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
63
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 14 publications
6
63
1
Order By: Relevance
“…TG was kept fixed at 1350 o C for all the four growths. A broad and weak hBN (002) plane peak was found at around 25.95 o for hBN grown without a nitridated layer buffer and it corroborates previous reports [10,11] that sp 2 -BN grown on non nitridated sapphire substrates is of poor crystalline quality. Sapphire nitridation at a temperature of 850 o C resulted in a much better film as far as the X-ray diffraction is concerned, with the hBN (002) peak at 26.7 o with a full width at half maximum (FWHM) value of 0.25 o .…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…TG was kept fixed at 1350 o C for all the four growths. A broad and weak hBN (002) plane peak was found at around 25.95 o for hBN grown without a nitridated layer buffer and it corroborates previous reports [10,11] that sp 2 -BN grown on non nitridated sapphire substrates is of poor crystalline quality. Sapphire nitridation at a temperature of 850 o C resulted in a much better film as far as the X-ray diffraction is concerned, with the hBN (002) peak at 26.7 o with a full width at half maximum (FWHM) value of 0.25 o .…”
Section: Resultssupporting
confidence: 90%
“…The precursors were triethylboron (TEB) for boron and ammonia (NH3) for nitrogen. Direct CVD growth of single crystal sp 2 -BN on c-axis oriented sapphire is difficult, if not impossible; previous works showed that only turbostratic BN (tBN), a disordered sp 2 -BN phase and an intermediate between sp 2 -BN and amorphous BN (aBN), is formed when directly grown on sapphire [10,11]. In-plane * Corresponding author: e-mail ahmedk2@rpi.edu, Phone: +15189619314 lattice constants of hBN and sapphire are 2.5 Å and 4.758 Å, respectively, indicating a large lattice mismatch [10].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Prior to the thin film deposition both type of substrates were in situ pretreated, where an AlN buffer layer was formed on -Al 2 O 3 by nitridation at the applied growth temperature using ammonia at a total concentration 10 % in hydrogen during 10 minutes 24 or by the introduction of silane into the reactor at the temperature of 950 °C in order to improve the 6H-SiC substrate surface morphology 29 .…”
Section: Methodsmentioning
confidence: 99%